The influence of nickel grade and its occurrence state on high pressure acid leaching behavior of lateritic nickel ores - Baking, Aad Alief Rasyidi; Zhou, Lejun; Liu, Wei (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
This research evaluates the effects of nickel grade and occurrence state on the leaching behavior of lateritic nickel ores using high-pressure acid leaching (HPAL) at 250 °C with sulfuric acid. Three ores were selected for the study: Ore 1 (ultra-low-grade limonite, 0.73 wt.% Ni), Ore 2 (limonite, 1.34 wt.% Ni), and Ore 3 (saprolite, 2.00 wt.% Ni). Mineralogical studies (XRD, SEM, and EPMA) were conducted to provide insight into nickel-hosting phases and characteristics of the ore matrix. A higher nickel grade does not necessarily result in higher extraction. Ore 1 had the lowest nickel grade but achieved the highest extraction of Ni (97.25%) and Co (98.49%) under experimental conditions using an acid-to-ore (A/O) ratio of 0.40. This significant Ni extraction is attributed to nickel’s structural substitution in goethite, an iron oxide mineral that dissolves readily under the HPAL process. Ore 2 also contains goethite as the dominant phase and achieved similarly high recoveries of Ni (97%) and Co (98%), however, Co recovery decreased slightly under higher acid conditions due to co-precipitation with hematite. Ore 3 had the highest nickel grade but the lowest leaching efficiency (<90% Ni). The generally low recoveries may be attributed to nickel being hosted in both goethite (a leachable phase) and lizardite (a less leachable phase). The silicate matrix of lizardite and its elevated magnesium content restricted the effective acid range and thus diminished nickel selectivity during the HPAL leaching process. The results highlight that the mineralogical occurrence state of nickel is more important than nickel grade in determining leaching performance. Therefore, low-grade limonite ores with favorable mineralogy can serve as potential feed sources for environmentally friendly sustainable nickel hydrometallurgical extraction.